(untitled) (European Journal of Health Research, 2020)
Anxiety is one of the most frequent psychiatric disorders. Coping refer to the different ways in which people face stressful situations. Research indicates that the greater the anxiety, the less use of adaptive strategies and the greater use of maladaptive strategies. The general objective is to determine if there is a relationrelate between anxiety and coping strategies. Two samples of participants have been used, with an incidental sample: clinical population (PC) diagnosed with an anxiety disorder (n = 35) and non-clinical population (PNC) not attended to psychologically treatment or diagnosed with anxiety (n = 38). The instruments administered were a sociodemographic questionnaire, the Goldberg Anxiety and Depression Scale and the Inventory of Coping Strategies. Regarding the results, significant differences were found in the use of adaptive or active strategies, the PC used this type of strategies less than the PNC. In addition, the strategy of cognitive restructuring, contributed significant differences, being less used by the PC than by the PNC. The PC was divided into two: one with depressive symptomatology and the other without it, the use of maladaptive coping strategies in the first group being significantly greater than the second. In conclusion, patients with an anxiety disorder use adaptive strategies less than the population without diagnosis, especially cognitive restructuring.